Pengaruh Gaya Kepemimpinan dan Motivasi Kerja terhadap Kinerja Karyawan Fakultas Ilmu Keolahragaan dan Kesehatan Universitas Negeri Jakarta - Andi Saputro; Zahra Zahra (Sekolah Tinggi Ilmu Ekonomi Cendekia Bojonegoro, 2025)
This study examines how leadership style and work motivation can affect employee performance at FIKK UNJ. The method used in this study is statistical quantitative data with data collection methods through observation, questionnaires, and documentation methods. In addition, the sampling technique used is a saturated sample where the entire population of fifty people was sampled. The data was processed using SPSS 26 with the results of the study showing that partially using the t test, leadership style and work motivation have a significant influence on employee performance. Simultaneously with the F test, leadership style and work motivation have a positive and significant influence on employee performance. These findings indicate that both independent variables have an important contribution in improving employee performance.